Automated Thrombin Generation Assay for Rivaroxaban, Apixaban, and Edoxaban Measurements - Meihandoest, Tamana; Studt, Jan-Dirk; Mendez, Adriana; Alberio, Lorenzo; Fontana, Pierre; Wuillemin, Walter A.; Schmidt, Adrian; Graf, Lukas; Gerber, Bernhard; Maeder, Gabriela Monika; Bovet, Cédric; Sauter, Thomas C.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background The thrombin generation assay (TG) is a promising approach to measure the degree of anticoagulation in patients treated with direct oral anticoagulants (DOAC). A strong association with plasma drug concentrations would be a meaningful argument for the potential use to monitor DOAC. Objectives We aimed to study the correlation of TG with rivaroxaban, apixaban, and edoxaban drug concentrations in a large, prospective multicenter cross-sectional study. Methods Five-hundred and fifty-nine patients were included in nine tertiary hospitals. The Technothrombin® TG was conducted in addition to an anti-Xa assay; LC-MS/MS was performed as the reference standard. Results Correlation (rs) between thrombin generation measurements and drug concentrations was -0.72 for peak thrombin generation (95% confidence interval, CI, -0.77, -0.66), -0.55 for area under the curve (AUC; 95% CI -0.61, -0.48), and 0.80 for lag time (95% CI 0.75, 0.84). In contrast, rs was 0.96 with results of the anti-Xa activity (95% CI 0.95-0.97). Sensitivity with regard to the clinically relevant cut-off value of 50 µgL-1 was 49% in case of peak thrombin generation (95% CI, 44, 55), 29% in case of AUC (95% CI, 24, 34), and 64% in case of lag time (95% CI, 58, 69). Sensitivity of the anti-Xa assay was 95% (95% CI, 92, 97). Conclusions The correlation of thrombin generation measurements with DOAC drug concentrations was weak, and clinically relevant drug levels were not predicted correctly. Our results do not support an application of TG in the monitoring of DOAC.